SOLVING OF QUASILINEAR EQUATION OF HEAT CONDUCTION TAKING INTO ACCOUNT TEMPERATURE DEPENDENCES OF DENSITY, AND HEAT CONDUCTION - S. L. Gavrilenko; S. V. Shilko; S. M. Kabishov; Ju. M. Pleskachevski; V. I. Timoshpolski (Литьë и металлургия, 2007)
The methods of calculation of the prismatic steel slug temperature field at heating in furnace is stated. The numerical solution of quasi-linear equation of heat conduction with granite conditions of the third type taking into account temperature dependence of the main thermal-physical characteristics (firmness, specific heat capacity and heat conduction) is received. The coefficients of heat transfer, at which experimental data and calculated values have minimum deviation, are determined.